THE WOODWORKING MACHINERY DURABILITY AND METHODS FOR ITS ENHANCING (Innovation in Woodworking Industry and Engineering design, 2026)
On the basis of previous theoretical and experimental studies by the author of this paper, the concept of the woodworking machinery's durability and methods for its enhancing is theoretically analyzed (presented) as one of the properties for its reliability. The coefficient of the woodworking machinery's durability - ηт in their lifecycle for the first time is described as a dimensionless value, always less then a unity. This factor takes into account the really accomplished works and the time, needed for repairs and downtime. The ratio ηт can be widely used in theoretical studies, related to kinematics and dynamics of various mechanisms and mechanic systems in the woodworking machinery, in analyzing and working out constructive solutions about the assembly of such machines. The technical resources and exploitation period are the durability's properties. Due to this methodology, conditions for mathematical description and analysis have been established.Based on these facts and from the previous theoretical analyses some specific methods for growing the woodworking machinery's durability are presented, as well as some recommendations for their applications. In theoretical analyses and studies on woodworking machinery mechanical systems this methods will be useful enough in most cases.